Avances en micro y nanoencapsulación de componentes bioactivos - Sifuentes Pacaya, Konny Corina (2022)
Micro and nanoencapsulation over the years have been responsible for studying in an interdisciplinary way the manipulation and preparation of various materials in certain dimensions (1 and 100 nm), as well as the search for new techniques or technological uses in bioactive compounds. These methods contribute to forge an encouraging panorama regarding the potential applications they can have in the different fields, especially within the food industries, thus being their main objective the protection of the material or product that has been encapsulated, among its main advantages are the gradual release of the product, allowing to possess adequate organoleptic and nutritional properties, it also allows the transformation of active substances. One of the methodologies or techniques of application are based on chemical and mechanical elements. Finally, after the analysis of information, it was concluded that the microencapsulation of bioactive materials can improve their delivery and release, making it a widely used tool in the development of "smart" products that facilitate and improve daily life by playing an active role in the process of use for different sectors such as food, pharmaceutical and cosmetic.